Calanus oil in the treatment of obesity-related low-grade inflammation, insulin resistance, and atherosclerosis - Gasmi, Amin; Mujawdiya, Pavan Kumar; Shanaida, Mariia; Ongenae, Adrien; Lysiuk, Roman; Doşa, Monica Daniela; Tsal, Oxana; Piscopo, Salva; Chirumbolo, Salvatore; Bjørklund, Geir (Applied Microbiology and Biotechnology, 2020)
Calanus oil (COil) is a natural product extracted from marine zooplankton Calanus finmarchicus found in the North Atlantic Ocean. This oil is rich in wax esters of polyunsaturated fatty acids (PUFAs) and has been projected as the best alternative to fish oil because its production cannot keep pace with the demands from the growing markets. The COil is the only commercially available marine source of wax esters, whereas classic ω-3 PUFAs comes from triglycerides, ethyl esters, and phospholipids. It has, in recent decades, been seen that there is an unprecedented rise in the use of PUFA-rich oil in the aquaculture industry. A simultaneous rise in the demand of PUFAs is also observed in the health care industry, where PUFAs are suggested preventing various disorders related to lifestyles such as obesity, diabetes mellitus, chronic low-grade inflammation, atherosclerosis, and brain and cardiovascular disorders (CVDs). In this review, we will explore the metabolic aspects related to the use of COil as an antioxidant, anticholesterinemic, and anti-inflammatory dietary source and its impact on the prevention and therapy of obesity-related metabolic disorders.